Conceptual Framework for the Definition and Regulation of Virtual Currencies: International and Russian practices - S. Belomyttseva, Olga (Naše gospodarstvo/Our economy, 2015)
This paper analyzes possible definitions of virtual currencies in legislation and economics. Views of the European Central Bank, Financial Crimes Enforcement Network, and Financial Action Task Force regarding virtual currencies are studied. The analysis also covers the draft legislation to ban money surrogates in the Russian Federation. The author suggests two reasonable approaches to defining virtual currencies in law and economics. The Austrian School representatives’ arguments on the existence of private money are reviewed. The author proposes the introduction of some changes in the legislation of the Russian Federation in order to give legal status to virtual currencies.